Advances in the Research on Anticardiolipin Antibody. (1st December 2019) - Wang, Dan; Lv, Wenxin; Zhang, Shichang; Zhang, Jiexin
Abstract : Anticardiolipin antibody (ACA) is a kind of autoantibody and is one of the antiphospholipid antibodies (aPLs). Phospholipids with a negative charge on platelets and endothelial cell membranes are ACA target antigens. ACA is common in systemic lupus erythematosus and other autoimmune diseases and is closely associated with thrombosis, thrombocytopenia, and spontaneous abortion. In 1983, Harris established a method for detecting ACA, and research on the antibody has gained worldwide attention and has developed rapidly. For this review, we browsed articles that cover most of the ACA-related studies in the last 25 years and extracted influential ideas and conclusions in this field.